2018
DOI: 10.1161/circulationaha.116.027034
|View full text |Cite
|
Sign up to set email alerts
|

Value of Progression of Coronary Artery Calcification for Risk Prediction of Coronary and Cardiovascular Events

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
115
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(120 citation statements)
references
References 53 publications
1
115
1
3
Order By: Relevance
“…Recently, a number of new measures for quantifying the added value from new markers were proposed, including the IDI and the NRI. These two measures have drawn much attention in the medical research, especially in the evaluation of markers for cardiovascular disease progression [11][12][13] . We used the NRI and IDI to quantify the improved survival prognostication for all confirmed prognostic factors incorporated into the TNM staging system.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a number of new measures for quantifying the added value from new markers were proposed, including the IDI and the NRI. These two measures have drawn much attention in the medical research, especially in the evaluation of markers for cardiovascular disease progression [11][12][13] . We used the NRI and IDI to quantify the improved survival prognostication for all confirmed prognostic factors incorporated into the TNM staging system.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery calcification has been reported to be an important predictor of significant coronary artery stenosis [10,[19][20][21][22]. Until now, only some risk-predicting score systems such as the Multi-Ethnic Study of Atherosclerosis risk score implanted CACS into their models, even though a recent study reported that CACS is the most important predictor of CAD-related outcomes [23].…”
Section: Discussionmentioning
confidence: 99%
“…Увеличение коронарного кальция более 400 на втором ýтапе исследования приводило к почти двукратному повышению риска коронарных и общих сердечно-сосудистых событий по сравнению с лицами, у которых уровень данного показателя при повторной КТ не превышал 400. У пациентов с нулевым уровнем кальция на двух ýтапах КТ 10-летний риск составил 1,4; 2,0 и 2,8% [30].…”
Section: оценка коронарной кальцифика-ции и прогноз риска отдаленных unclassified